In vivo placental MRI shape and textural features predict fetal growth restriction and postnatal outcome - Dahdouh, Sonia (J Magn Reson Imaging, 2017)
PURPOSE: To investigate the ability of 3D MRI placental shape and textural features to predict fetal growth restriction (FGR) and birth weight (BW) for both healthy and FGR fetuses. MATERIALS AND METHODS: We recruited two groups of pregnant volunteers between 18 and 39 weeks of gestation; 46 healthy subjects and 34 FGR. Both groups underwent fetal MR imaging on a 1.5T GE scanner using an 8-channel receiver coil. We acquired T2-weighted images on either the coronal or the axial plane to obtain MR volumes with a slice thickness of either 4 or 8mm covering the full placenta. Placental shape features (volume, thickness, elongation) were combined with textural features; first order textural features (mean, variance, kurtosis and skewness of placental grey levels), as well as, textural features computed on the grey level co-occurrence and run-length matrices characterizing placental homogeneity, symmetry and coarseness. The features were used into two machine learning frameworks to predict FGR and BW. RESULTS: The proposed machine-learning based method using shape and textural features identified FGR pregnancies with 86% accuracy, 77% precision and 86% recall. BW estimations were 0.3 ± 13.4% (mean percentage error ± standard error) for healthy fetuses and −2.6 ± 15.9% for FGR. CONCLUSION: The proposed FGR identification and BW estimation methods using in utero placental shape and textural features computed on 3D MR images demonstrated high accuracy in our healthy and high-risk cohorts. Future studies to assess the evolution of each feature with regard to placental development are currently underway.